Diagnosis and treatment of chronic synovitis in patients with haemophilia: consensus statements from the Italian Association of Haemophilia Centres. (19th December 2021) - Di Minno, Matteo Nicola Dario; Napolitano, Mariasanta; Giuffrida, Anna Chiara; Baldacci, Erminia; Carulli, Christian; Boccalandro, Elena; Bruno, Clarissa; Forneris, Eleonora; Ricca, Irene; Passeri, Walter; Martinelli, Marco; Rivolta, Gianna Franca; et al.
Summary: Although synovitis is recognized as a marker of joint disease activity, its periodic assessment is not included in routine clinical surveillance of patients with haemophilia (PwH). In order to evaluate the current knowledge and to identify controversial issues, a preliminary literature search by the Musculoskeletal Committee of the Italian Association of Haemophilia Centres (AICE) has been conducted. Statements have been established and sent to the Italian AICE members to collect their level of agreement or disagreement by a Delphi process. Thirty‐seven consensus recommendations have been drafted. We found a general agreement on the indication to consider the presence of synovitis as a marker of joint disease activity in PwH. Accordingly, there was agreement on the indication to search for synovitis both in patients reporting joint pain and in asymptomatic ones, recognizing ultrasound as the most practical imaging technique to perform periodic joint screening. Interestingly, after detection of synovitis, there was agreement on the indication to modify the therapeutic approach, suggesting prophylaxis in patients treated on demand and tailoring treatment in patients already under prophylaxis. Whereas the need of an early consultation with a physiotherapist is recommended for PwH affected by chronic synovitis, the exact timing for an orthopaedic surgeon consultation is currently unknown.